ANALYSIS OF ENVIRONMENTAL NOISE POLLUTION CAUSED BY GAS PUMPING UNITS IN BLOCK-CONTAINER DESIGN - Semchuk, Ya. M.; Kryvenko, G. M.; Lialiuk-Viter, G. D.; Shymanskyi, V. Ya.; Kryvenko, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
Compressor stations play a crucial role in the technological processes of hydrocarbon energy carrier preparation and transportation. However, they are also significant sources of environmental pollution. The expansion of gas pipeline networks, particularly those located near residential areas, has created a serious ecological concern, as the noise generated by compressor stations contributes to environmental degradation. Exceeding permissible noise levels established by current sanitary standards adversely affects both the operational personnel of compressor stations and residents of nearby communities. Therefore, mitigating various types of noise produced by gas transport equipment is a critical social issue. This study aims to investigate environmental noise pollution caused by gas pumping units in block-container configurations. To achieve this goal, the research focuses on identifying the primary noise sources of such units and evaluating their environmental impact. Gas pumping units in block-container design are widely used for the transportation of natural gas, and it should be noted that they exhibit high levels of sound power, which negatively affect the environment. Consequently, noise reduction and improved working conditions during the operation of these units are particularly relevant. Effective implementation of noise mitigation measures requires a comprehensive understanding of the physical nature of key noise sources, as well as the mechanisms of sound generation and propagation throughout the gas pumping unit. Research findings indicate that intake and exhaust ducts, the walls of engine and compressor compartments, pipeline systems, and fans are the main sources of noise. An analysis of the acoustic characteristics of block-container units was conducted. The primary contributors to noise levels within industrial and residential areas are gas-air pathways, the container itself, and the associated pipeline systems. Enhancing the sound insulation of containers and pipeline systems represents a key strategy for mitigating noise emissions from gas pumping units.